The MMPI-2 and client feedback: a quantitative investigation and exploratory analysis of feedback models - El-Shaieb, Muna, author; Vacha-Haase, Tammi, advisor; Thornton, George C., III, committee member; Cobb, Brian, committee member; Davidshofer, Charles O., committee member (Colorado State University. Libraries, 2005)
This study investigated the effects of 2 different kinds of feedback in the context of a MMPI-2 personality assessment on symptoms, self-esteem, process variables, and an open-ended survey. Participants were clients seeking counseling from an outpatient clinic and a university counseling center. Symptoms, self-esteem, session impact, counselor influence, and ratings of the assessment were evaluated by clients using the Rosenberg Self-Esteem Scale (RSES), Outcome Questionnaire (OQ-45.2), Session Evaluation Questionnaire (SEQ), Counselor Rating Form (CRF), Assessment Questionnaire (AQ), and an open-ended survey developed by the author. Participants (N = 33) were randomly assigned to 1 of 3 groups: interactive feedback, delivered feedback and control. Participants in the feedback groups had 3 sessions with a counselor, 1 per week for 3 weeks. Sessions included an intake session (week 1) followed by completion of the MMPI-2, a feedback session (week 2), and a follow-up session (week 3). Feedback groups completed symptom, self-esteem, and process measures at every session, and symptom, self-esteem and an open-ended survey 4 weeks post-treatment. The control group completed the MMPI-2, had treatment delayed for 3 weeks, and then completed an intake session, followed with a feedback session 1 week later. The control group completed symptom and self-esteem measures at week 1, week 2, and week 3, and symptom, self-esteem, and process measures at intake and feedback sessions. Participants' feedback sessions consisted of MMPI-2 results given in either an interactive manner, which encouraged the client to collaborate on feedback, or a delivered manner, with minimal client participation. Clients in the 2 feedback groups did not exhibit differences for symptoms or self-esteem. Significant differences were found for process variables: interactive group clients reported higher ratings for second session depth, positivity, arousal, and overall satisfaction with the assessment as compared to delivered group clients. Interactive group clients also reported higher ratings for third session counselor influence as compared to the delivered group clients. No differences were found between the 2 feedback groups for answers on the open-ended survey. Results suggested that counselors should consider an interactive feedback style as it positively impacts clients' perceptions of the counselor, session, and assessment.
Keywords: psychotherapy; clinical psychology